Enhanced Th17 responses in the appendix of children with complex compared to simple appendicitis are associated with microbial dysbiosis - The, Sarah-May M. L.; Schreurs, Renée R. C. E.; Drewniak, Agata; Bakx, Roel; de Meij, Tim G. J.; Budding, Andries E.; Poort, Linda; Cense, Huib A.; Heij, Hugo A.; van Heurn, L. W. Ernest; Gorter, Ramon R.; Bunders, Madeleine J. (Frontiers in Immunology, 2024)
Introduction: Appendicitis is one of the most common causes of acute abdominal surgery in children. The clinical course of appendicitis ranges from simple to complex appendicitis. The mechanisms underlying the heterogeneity of appendicitis in children remain largely unclear. Dysregulated T cell responses play an important role in several inflammatory diseases of the intestine, but the extend of T cell dysregulation in appendicitis in children is less well known. Methods: To characterize appendiceal T cells in simple and complex appendicitis we performed in-depth immunophenotyping of appendiceal-derived T cells by flow cytometry and correlated this to appendiceal-derived microbiota analyses of the same patient. Results: Appendix samples of twenty children with appendicitis (n = 8 simple, n = 12 complex) were collected. T cells in complex appendicitis displayed an increased differentiated phenotype compared to simple appendicitis, including a loss of both CD27 and CD28 by CD4+ T cells and to a lesser extent by CD8+ T cells. Frequencies of phenotypic tissue-resident memory CD69+CD4+ T cells and CD69+CD8+ T cells were decreased in children with complex compared to simple appendicitis, indicating disruption of local tissue-resident immune responses. In line with the increased differentiated phenotype, cytokine production of in particular IL-17A by CD4+ T cells was increased in children with complex compared to simple appendicitis. Furthermore, frequencies of IL-17A+ CD4+ T cells correlated with a dysregulation of the appendiceal microbiota in children with complex appendicitis. Conclusion: In conclusion, disruption of local T cell responses, and enhanced pro-inflammatory Th17 responses correlating to changes in the appendiceal microbiota were observed in children with complex compared to simple appendicitis. Further studies are needed to decipher the role of a dysregulated network of microbiota and Th17 cells in the develop-ment of complex appendicitis in children.